Movements of exclusion : radical right-wing populism in the Western world - Rydgren, Jens 1969- Hrsg (Nova Science Publishers, 2005)
Verlagsinfo: The last two decades have seen the emergence of new radical right-wing populist parties in Western democracies. The electoral breakthrough of the French Front National in 1984 was the starting point for the rise of parties combining anti-establishment populism and anti-immigrant politics based on ethno-nationalist ideology, and today radical right-wing populist parties are well represented in national politics in Austria, Belgium, Denmark, France, Italy, Norway, Switzerland, and the Netherlands in Western Europe, as well as in Australia, Canada, and New Zealand. By bringing together some of the foremost experts within this area of research, this book gives a comprehensive image of different aspects of radical right-wing populism: its causes, ideology, and impact.